Mengapa Akuntan Tidak Berbohong? Studi Eksperimen pada Perilaku Budgetary Slack - Dewi Sukmasari; Yenni Agustina; Aryan Danil Mirza. BR (Jurnal Akuntansi dan Pajak, 2023)
Individual performance evaluation is usually measured based on his success in achieving targets in organizations. Thus, budget has major influence on individual behavior in organizations. Organization strives to create the most appropriate budgeting system to accommodate the interests of the company, department or business unit and individuals within it. This is because budgeting will have an impact on individual performance which in turn will also have an impact on company performance. Budgetary slack is one of the main problems that often arise in the budgeting process. The gap between the best estimate of performance and the proposed budget causes the company to lose out on getting the maximum performance potential of individuals and profits for the company. In addition, the social pressure causes individuals to behave in a way that deviates from company values. Individuals who experience very strong pressure from both superiors and coworkers will increase the individual's chances of committing unethical actions (budgetary slack). But on the other hand, several studies show that not all individuals are obedient to social pressure from others. Most individuals, especially accountants, refuse to commit unethical actions even though the threat of very severe punishment awaits. We are interested in analyzing this unique phenomenon. Using the experimental research on 90 participants, we found evidence that different levels of individual locus of control can minimize the occurrence of budgetary slack. The results of this study are expected to provide consideration for stakeholders in the financial sector to consider individual personal values as one of the important variables that play a role in budgeting success in companies or organizations.